TITAN CSR: a new self-retaining retractor for abdominal surgery - Brian Eastridge; Erika Paola Brigmon (Trauma Surgery & Acute Care Open, 2023)
Background Self-retaining retractors provide hands-free exposure and allow surgeons to use their hands to perform surgery rather than manually retract tissues. Non-table-mounted retractors offer rapid assembly, but they have been traditionally limited in their ability to provide adequate exposure of the abdomen. Table-mounted retractors provide excellent exposure, but their cumbersome and time-intensive assembly often precludes their use in emergency settings. The TITAN CSR surgical retractor is a novel, lightweight, expandable, and modular system which offers the benefits of both designs by providing rapid assembly and effective abdominal exposure without a table attachment. We describe our experience with this new retractor system.Methods Retrospective case series of selected trauma and emergency surgery laparotomies at an urban academic level 1 trauma center using the TITAN CSR surgical retractor during a 1-year period.Results The TITAN CSR surgical retractor was used to provide exposure for trauma and emergency surgery laparotomies in both adult and pediatric patients in 89 cases from July 2021 to July 2022. Without requiring a table attachment, the TITAN CSR retractor provided hands-free surgical exposure during a variety of procedures including traumatic hysterectomy, gastrorrhaphy, enterorrhaphies and colectomy. With the added utility of attaching Bookwalter-compatible retractor blades, it provided effective exposure of retroperitoneal structures. These structures included the inferior vena cava, left femoral vessels, and duodenum. All laparotomies presented were successfully completed without setting up a post or a connection to the surgical table.Discussion The TITAN CSR surgical retractor was successfully used in a number of difficult trauma and emergency surgery laparotomies, providing effective intra-abdominal and retroperitoneal exposure without necessitating an attachment to the surgical table. This retractor has the potential to replace current retractor systems in abdominal surgery, providing the benefits of table-mounted and non-table-mounted designs while removing their various disadvantages.